Sweetest thing - U2; Lillywhite, Steve; PolyGram International Music (United Kingdom : PolyGram International Music, 1998)
Contains the single pop rock track.
CD 1 : Sweetest thing / (3:00)
Koleksi Khas Wiramanja.
Title from the container.
Keywords: Songs, English